Mapping ecosystem service temporal trends: a case study of European wood potential, supply and demand between 2008 and 2018 - Poturalska, Anita; Alahuhta, Janne; Kangas, Katja; Ala-Hulkko, Terhi (Pensoft Publishers, 2024)
Wood is one of the key forest Ecosystem Services (ES) of growing ecological, social and economic importance; therefore, we need more precise information about its long-term usage. To achieve this, it is necessary to examine the spatio-temporal aspects of wood ES potential, supply and demand. In this study, we analyse spatio-temporal patterns of wood ES supply and demand at continental, national and regional scales to identify areas of increasing and decreasing supply and demand levels in Europe. In addition, we present background information about the potential of European forests to provide wood ES and its relationship to supply and demand. Our results showed that the overall European wood supply and demand as well as the wood ES potential were characterised by increasing trends. Furthermore, this increase was also regional, particularly in central and northern Europe. This study demonstrates not only the significance of spatio-temporal data in ES mapping, but also the importance of considering a broader range of components of the ES cascade model when assessing change. Our research has shown that potential, supply and demand can all increase in the same area, but also that low supply and demand do not guarantee wood potential growth. In addition, we found that a broad scale assessment helps to identify more general patterns and trends, but analysing data at a more accurate scale provides more comprehensive insights for identifying areas that may require targeted action for sustainable forest management.
Keywords: wood ecosystem service; temporal change; spatial distribution; wood ecosystem service potential; wood ecosystem service supply; wood ecosystem service demand